2011
DOI: 10.1186/gm268
|View full text |Cite
|
Sign up to set email alerts
|

Genetics and genomics of radiotherapy toxicity: towards prediction

Abstract: Radiotherapy is involved in many curative treatments of cancer; millions of survivors live with the consequences of treatment, and toxicity in a minority limits the radiation doses that can be safely prescribed to the majority. Radiogenomics is the whole genome application of radiogenetics, which studies the influence of genetic variation on radiation response. Work in the area focuses on uncovering the underlying genetic causes of individual variation in sensitivity to radiation, which is important for effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
135
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(141 citation statements)
references
References 121 publications
1
135
0
5
Order By: Relevance
“…Sildenafil is a selective and potent inhibitor of cyclic guanosine monophosphate (cGMP)-specific phosphodiesterase (PDE)-5, which catalyzes the hydrolysis of cGMP and has a relaxant effect on the smooth muscle cells of the arterioles supplying the human corpus cavernosum 24 . The data of a recent study have shown that sildenafil, acting via a nitric oxide (NO)-dependent mechanism, prevented indomethacin-induced gastropathy, possibly through a reduction of leukocyte adhesion and maintenance of gastric blood flow 25 . Two studies by Iseri and Yildirim et al 26,27 demonstrated the beneficial anti-inflammatory actions of sildenafil on acetic acid-induced acute colitis and bleomycin-induced lung fibrosismodels in rats via prevention of lipid peroxidation, oxidant generation, cytokine production and neutrophil accumulation.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sildenafil is a selective and potent inhibitor of cyclic guanosine monophosphate (cGMP)-specific phosphodiesterase (PDE)-5, which catalyzes the hydrolysis of cGMP and has a relaxant effect on the smooth muscle cells of the arterioles supplying the human corpus cavernosum 24 . The data of a recent study have shown that sildenafil, acting via a nitric oxide (NO)-dependent mechanism, prevented indomethacin-induced gastropathy, possibly through a reduction of leukocyte adhesion and maintenance of gastric blood flow 25 . Two studies by Iseri and Yildirim et al 26,27 demonstrated the beneficial anti-inflammatory actions of sildenafil on acetic acid-induced acute colitis and bleomycin-induced lung fibrosismodels in rats via prevention of lipid peroxidation, oxidant generation, cytokine production and neutrophil accumulation.…”
Section: ■ Discussionmentioning
confidence: 99%
“…It is commonly known that radiation involves the formation of reactive oxygen species and reactive nitric oxide species, which induce stress responses and inflammation, as well as the release of cytokines, growth factors and chemokines. The production of free radicals following exposure to ionizing irradiation causes DNA damage 25 . In our study, immunoreactivities of IL-1β, FGF-2, TNF-α and HIF-1α increased in the control group of ARP especially in the epithelial and cryptic regions, compared to the treatment groups while VEGF reactivity of the control group also increased in stromal vessels, compared to other groups.…”
mentioning
confidence: 99%
“…The overriding motivation for predictive testing is to be able to tailor radiotherapy for an individual patient to improve outcome [76,77]. At first sight, altering treatment to reduce toxicity in the 10% most sensitive patients would seem to be the priority.…”
Section: Using Predictive Tests Of Normal Tissue Sensitivity To Altermentioning
confidence: 99%
“…Intrinsic radiosensitivity was measured by the survival fraction at 2 Gy (SF2), that is, the ability of a cell to undergo more than 5-6 cell divisions and produce a viable colony containing at least 50 cells after ionizing radiation exposure [3,4]. This assay is very laborious, time-consuming and technically challenging as it is highly dependent on factors such as the type of the medium, the serum concentration, and the technical skill of the investigator [5,6]. A high radiosensitivity inducing severe late effects implied mechanisms related to cell death and resulting from defective DNA repair.…”
Section: Biomarkers and Assays To Predict Normal Tissue Late Toxicitiesmentioning
confidence: 99%